Learner Autonomy as a Challenge in English Language Education 4.0 in Indonesia - Agustina, Dwi; Fajar, Dwi Ario (Universitas Muhammadiyah Semarang, 2018)
The development of technology has enriched the educational practices in many settings including in Indonesia. The use of technology has contributed a lot to many teaching and learning activities both inside and outside the classrooms in Indonesian contexts, especially in foreign language education like English. This is likely to be a good sign to welcome English language education 4.0. However, the success of English language education 4.0 also depends also on students’ readiness to be more independent or autonomous in their English learning. Our qualitative study has revealed that students in English education department still have difficulties in maintaining their autonomy level in learning. The learner autonomy is dynamic in the way that its level keeps changing. This may turn into a particular challenge for the enactment of English language education 4.0 if the students are not equipped with the skills to maintain their autonomy level in their English learning.